Using choice theory-based instruction to foster vocabulary learning. Issue 1 (2nd January 2021) - Marashi, Hamid; Erami, Neda
ABSTRACT: This study was an attempt to investigate the effect of choice theory-based instruction on Iranian EFL learners' vocabulary achievement. To fulfil the purpose of this study, 60 female advanced EFL learners were selected from among a total number of 90 learners through their performance on a piloted sample Cambridge ESOL Certificate of Advanced English test. The learners were assigned into two control and experimental groups, each with the same number of students (30). A teacher-made vocabulary test was given to both groups to identify the words that the learners knew prior to the treatment; subsequently, those words were not included in the treatment. Both groups sat in class for 18 sessions of 90 minutes each and were taught the same materials. In the experimental group, the students underwent the treatment based on choice theory principles, whereas the learners in the control group received the instruction which was based on the syllabus of the language school. A modified version of the same vocabulary achievement test used at the outset was administered as the posttest at the end of the treatment to both groups. The mean scores of the two groups on this posttest were compared through an independent samples t- test . The results showed that choice theory-based instruction had a significantly positive effect on EFL learners' vocabulary achievement. Accordingly, this study suggests the application of choice theory-based instruction in the ELT environment.